PENGEMBANGAN FORMULASI LULUR BIJI JINTAN HITAM - Mirawati Mirawati (As-Syifaa Jurnal Farmasi, 2009)
An investigation on formulation of body scrub from Nigella sativa seed has been carried out. The purpose of this investigation was to determine which formula stability optimal. Body scrub made emulsi which were amulsified by anionic group sulphate emulsifier, anionic group amine emulsifier, and nonionic emulsifier than determined the stability of body scrub with stress condition. Parameters investigated were emulsi type, viscocity and droplet size determined. The results showed that emulsi type from three formulas were oil in water (o/m) emulsion both before and after stress condition. Droplet size showed increased after stress condition. Viscocity from three formulas after stress condition showed reduced significantly (α = 0.01) but body scrub with anionic group sulphate emulsifier showed reduction only in α = 0.05. The conclusion showed that body scrub with anionic group sulphate emulsifier was relative the most stable emulsion.Keywords: Emulsifier, Nigella sativa seed, stability